Dampak Sosial dan Ekonomi Aktivitas Penambangan Batu Split di Kecamatan Tabukan Utara Kabupaten Kepulauan Sangihe - Sandri Reza Lawendatu; Helena Sri Sulastriningsih; Xaverius Erick Lobja; Ellen Eva Poli (Fakultas Ilmu Sosial dan Hukum, 2023)
This study aims to describe the social and economic conditions of the split stone-picking community in Kalebuka 1 village and Kalebuka village. The research focus consists of social conditions, which include cooperation, and economic conditions, which include changes in people's living standards. The results showed that the extraction of split stones in the villages of Kalebuka 1 and Kalebuka had both positive and negative social and economic impacts. Positive social impacts include the establishment of cooperation, growing work motivation, an increase in income, and the occurrence of social interactions. While the social impact is negative, the occurrence of conflicts is due to fighting over land for split stone extraction. Extraction of split stone has an economic impact including becoming a source of income, increasing job opportunities, becoming a source of income in fulfilling needs, and opening up business opportunities so that it has an impact on people's welfare.